Velocity- and pointing-error measurements of a 300 000-r/min self-bearing permanent-magnet motor for optical applications - Breitkopf, Sven; Lilienfein, Nikolai; Achtnich, Timon; Zwyssig, Christof; Tunnermann, Andreas; Pupeza, Ioachim; Limpert, Jens (Review of Scientific Instruments, 2018)
Compact, ultra-high-speed self-bearing permanent-magnet motors enable a wide scope of applications including an increasing number of optical ones. For implementation in an optical setup, the rotors have to satisfy high demands regarding their velocity and pointing errors. Only a restricted number of measurements of these parameters exist and only at relatively low velocities. This manuscript presents the measurement of the velocity and pointing errors at rotation frequencies up to 5 kHz. The acquired data allow us to identify the rotor drive as the main source of velocity variations with fast fluctuations of up to 3.4 ns (RMS) and slow drifts of 23 ns (RMS) over ∼120 revolutions at 5 kHz in vacuum. At the same rotation frequency, the pointing fluctuated by 12 μrad (RMS) and 33 μrad (peak-to-peak) over ∼10 000 round trips. To our best knowledge, this states the first measurement of velocity and pointing errors at multi-kHz rotation frequencies and will allow potential adopters to evaluate the feasibility of such rotor drives for their application.
CRIS-Team Scopus Importer:2023-04-20